Pharmacotherapy or Psychotherapy? Selective Treatment Depression in The Infertile Women with Recurrent Pregnancy Loss: A Triple-Arm Randomized Controlled Trial - Zahra Basirat; Farzan Kheirkhah; Mahbobeh Faramarzi; Sedigheh Esmaeilzadeh; sorraya khafri; Zahra Tajali (International Journal of Fertility and Sterility, 2022)
Background: Recurrent pregnancy loss (RPL) and infertility are associated with significant psychiatric complications.The study aimed to investigate the effectiveness of cognitive behavioral therapy (CBT) and sertralinein the treatment of in depression, anxiety, and infertility stress of depressed infertile women with RPL in comparisonwith usual care.Materials and Methods: A triple-arm randomized controlled trial was carried out on the 60 depressed infertilewomen with RPL, a population of Infertility Center of Babol city, Iran, who were randomly assigned into threegroups: pharmacotherapy with sertraline (n=20), psychotherapy with CBT (n=20), and a usual care as controlgroup (n=20). The participants of psychotherapy received CBT sessions (90 minutes each) over 10 weeks. Theparticipants in the pharmacotherapy group took 50 mg/day sertraline daily for 22 weeks. Outcomes were assessedusing the Beck Depression Inventory (BDI-II), fertility problem inventory (FPI), and State-Trait AnxietyInventory Form Y (STAI-Y) at the beginning of the trial, 10-weeks post-trial, and three months of follow-up.Using statistical package for the social sciences (SPSS) software, data were analyzed.Results: CBT considerably reduced the depression symptoms more than sertraline with a moderate effect sizeat the post-trial (g=0.11, 95% CI: -0.03 to -0.50). Sertraline showed reduced the scores of state-anxiety moreconsiderably in comparison with control group by a large effect size of post-trial (g=-1.04, 95% CI: -1.70 to-0.38). CBT reduced the total scores of FPI more considerably than sertraline, with a large, small size at followup-trial [95% CI=-0.03(-0.65, -0.58)]. Both CBT and sertraline were superior to the control group in reducingdepression and infertility stress.Conclusion: Depression and infertility stress diminished under CBT and sertraline in depressed infertile women withRPL, with a signiﬁcant advantage of CBT. Sertraline was superior to CBT in reduction of anxiety (registration number:IRCT201304045931N3).